A Phase-2 Trial of Single Agent Axitinib as Maintenance Therapy Following First-Line Treatment With Modified FOLFOX/Bevacizumab in Patients With Metastatic Colorectal Cancer. (3rd July 2017) - Bendell, Johanna C.; Joseph, Mathew; Barnes, Kirk; Mainwaring, Mark; Shipley, Dianna; Reddy, Chandra; Blakely, Laura; Blachly, Ronald; Lane, Cassie M.; Earwood, Chris; Kuzur, Michel
ABSTRACT: This phase-2 trial evaluated the efficacy of axitinib as maintenance therapy for patients with metastatic colorectal cancer (mCRC) following first-line treatment with FOLFOX/bevacizumab. Patients with mCRC received mFOLFOX/bevacizumab followed by axitinib maintenance after four cycles. The primary endpoint was progression-free survival (PFS). Seventy patients were enrolled. Common treatment-related toxicities were fatigue, nausea, diarrhea, and peripheral neuropathy during FOLFOX/bevacizumab treatment; and fatigue, hypertension, diarrhea, and peripheral neuropathy during axitinib treatment. Median PFS was 8.3 months. Treatment with FOLFOX/bevacizumab followed by maintenance axitinib as first-line treatment for mCRC produced a median PFS consistent with historical controls of other first-line regimens.